2018
DOI: 10.1177/2325967118s00160
|View full text |Cite
|
Sign up to set email alerts
|

Jones Fracture in the Elite Athlete: Patient Reported Outcomes following Fixation with BMAC

Abstract: Objectives:Jones’ fractures, 5th metatarsal metaphyseal-diaphyseal junction fractures, are a debilitating injury for the elite athlete, particularly in cutting/pivoting sports. These injuries are usually managed surgically due to the high rate of nonunion and re-fracture. Despite primary screw fixation, delayed union and nonunion are not uncommon. Bone marrow aspirate concentrate (BMAC), an autologous source of hematopoietic and mesenchymal stem cells, has been used to augment healing due to the poor healing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…PROMIS PF and PROMIS PI improved significantly after surgery. While Carney et al [ 6 ] did not show specific PROMIS scores in their abstract, they noted improvement in PROMIS10 scores (a global PROMIS domain) at 12 months. In addition, they found that patients had significantly improved visual analog scores (VAS) for pain, foot and ankle ability measure (FAAM) scores, patient acceptable symptom state (PASS) at 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…PROMIS PF and PROMIS PI improved significantly after surgery. While Carney et al [ 6 ] did not show specific PROMIS scores in their abstract, they noted improvement in PROMIS10 scores (a global PROMIS domain) at 12 months. In addition, they found that patients had significantly improved visual analog scores (VAS) for pain, foot and ankle ability measure (FAAM) scores, patient acceptable symptom state (PASS) at 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 96%
“…However, controversy still exists on the mode of fixation required for optimal results. Current management techniques have shown the efficacy of intramedullary screw fixation [ 6 8 ] although the optimal characteristics of the screw (length and diameter) are still debated. This study aims to determine how better anatomical understanding translates to patient-reported outcomes using PROMIS CAT surveys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations